Purification and Characterization of the alpha-Glucosidase Produced by Thermophilic Fungus Thermoascus aurantiacus CBMAI 756 - Azevedo Carvalho, Ana Flavia [UNESP]; Boscolo, Mauricio [UNESP]; da Silva, Roberto [UNESP]; Ferreira, Henrique [UNESP]; Gomes, Eleni [UNESP] (Microbiological Society Korea, 2010)
An alpha-glucosidase enzyme produced by the fungus Thermoascus aurantiacus CBMAI 756 was purified by ultra filtration, ammonium sulphate precipitation, and chromatography using Q Sepharose, Sephacryl S-200, and Superose 12 columns. The apparent molecular mass of the enzyme was 83 kDa as determined in gel electrophoresis. Maximum activity was observed at pH 4.5 at 70 degrees C. Enzyme showed stability stable in the pH range of 3.0-9.0 and lost 40% of its initial activity at the temperatures of 40, 50, and 60 C. In the presence of ions Na(+), Ba(2+), Co(2+), Ni(2+), Mg(2+), Mn(2+), Al(3+), Zn(2+), Ca(2+) this enzyme maintained 90-105% of its maximum activity and was inhibited by Cr(3+), Ag(+), and Hg(2+). The enzyme showed a transglycosylation property, by the release of oligosaccharides after 3 h of incubation with maltose, and specificity for short maltooligosaccharides and alpha-PNPG. The K(m) measured for the a-glucosidase was 0.07 mu M, with a V(max) of 318.0 mu mol/min/mg.
Keywords: alpha-glucosidase; T. aurantiacus; termostable enzyme; transglycosylation reaction; Purification